Correlation between Central Corneal Thickness Measurements Using Two Different Ultrasonic Pachymeters - Khabir Ahmad, Sharmeen Akram, Zarksis H. Anklesaria (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess correlation between central corneal thickness measurements using two different ultrasonic pachymeters. Material and Methods: This prospective study involved normal subjects aged 16 to 45 years. Central corneal thickness was measured in 47 eyes by two ultrasonic pachymeters – Tomey SP – 100 and Sonomed 300 AP. Correlations between CCT measurements assessed by the two pachymeters were tested by Pearson correlation. Results: Forty seven eyes were included in the study. The mean (± SD) age of the subjects was 27.79 years (± 6.88).The mean (± SD) Tomey Pachymeter CCT was 536.45 m (34.37) and the mean (SD) Sonomed CCT was 540.64 m (33.48).CCT measurements by the two modalities were very strongly correlated (r = 0.98; P <0.0001). Conclusions: In healthy individuals, Tomey pachymeter measurements of corneal thickness were highly correlated with those obtained using Sonomed pachymeter, and hence the two may be used interchangeably.